Design and manufacture of ceramic heat pipes for high temperature applications. (22nd January 2015) - Meisel, Peter; Jobst, Matthias; Lippmann, Wolfgang; Hurtado, Antonio
Abstract: Heat exchangers based on ceramic heat pipes were designed for use under highly abrasive and corrosive atmospheres at temperatures in the range of 800–1200 °C for high-temperature power-engineering applications. The presented heat pipes are gravity assisted and based on a multi-layer concept comprising a ceramic cladding and an inner metal tube that contains sodium as the working fluid. Hermetical encapsulation of the working fluid was achieved by electron-beam welding of the inner metal tube. Subsequently, closure of the surrounding ceramic tube was performed by laser brazing technology using a glass solder. Temperature resistance and functionality of the manufactured ceramic thermosyphons could be confirmed experimentally in a hot combustion gas atmosphere at temperatures up to 1100 °C. The ceramic tubes used had an outer diameter of 22 mm and a total length of 770 mm. The measured axial heat transfer of the ceramic gravity assisted heat pipes at the stationary operating point with cold/hot gas temperature of 100 °C/900 °C was 400 W. The result of the calculation using the created mathematical model amounted to 459 W. Highlights: Heat-pipe design consists of a ceramic shell and an inner metallic tube. Laser brazing technology is suitable to seal ceramic heat-pipes. Thermal characteristic of double wall thermosyphon was modelled using FEM code. Experimental investigations demonstrated functionality of double wall thermosyphons.